Kadar seng dan kadar malondialdehyde pada penderita multi drug resistant tuberculosis dan tuberkulosis sensitif - Suparno, Suparno; Suhartono, Suhartono; Sofro, Muchlis Achsan Udji; Sulchan, Mohammad; Tjahjono, Kusmiyati (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2018)
Background: Zinc is the main constituent element of Superoxide Dismutase (SOD) which acts to protect cells from inflammation and the toxic effects of Reactive Oxygen Species (ROS). High ROS production induces fat peroxidation, and forms malondialdehyde (MDA) which causes oxidative stress.Objectives: This study aimed to analyze the difference of zinc and malondialdehyde levels among Multi Drug Resistant Tuberculosis and sensitive Tuberculosis.Methods: Crossectional study with 55 subjects consisted of 32 MDR-TB subjects and 23 subjects TB sensitive. Selection of subjects using consecutive sampling. Zinc and MDA serum was obtained from venous blood. Zinc and MDA concentration were assessed by quantitative colometric and Thiobarbituric Acid Reactive Substances (TBARS) respectively. Data were analized statistic by independent t-test and Mann Whitney test.Results: Zinc level of MDR-TB and TB sensitive were 74.85 (64 - 97) Î¼g/dl and 73.03 (63 - 97) Î¼g/dl respectively, while MDA of MDR-TB and sensitive TB were 2.262Â±1.055 nmol/mL and 2.66Â±0.992 nmol/mL. There was no significantly different in zinc level between MDR-TB and sensitive TB (p=1.000). Furthermore, there was not significantly different of MDA level between MDR-TB and sensitive Tuberculosis (p=0,147).Conclusion: There are no differences in zinc and MDA levels in patient between MDR-TB and sensitive TB.